2022
DOI: 10.31018/jans.v14i1.3332
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on seed protein fractions in chickpea, Cicer arietinum (L.)

Abstract: Worldwide, different abiotic stresses, such as drought, salinity, and heavy metals, harm crop productivity. Legumes, compared to cereals, are more susceptible to these stresses. The current work aimed to provide more insights into the effects of Cd and Pb on various seed protein characteristics of two cultivars of chickpea (Cicer arietinum), HC1 and HC5. At the highest concentrations of Cd, the total seed proteins decreased from 25.2% (control) to 7.1% (30 mg/kg soil), while in the case of the maximum concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…According to Farooq et al (2018), higher concentrations of heavy metals reduce the overall seed protein content in legumes. In addition, albumins and globulins, the seed protein fractions, have been reported to decrease under Cd supply in chickpeas(Ghosh et al, 2022). These findings also validate the conclusions ofChaoui and El Ferjani (2013) and Jaouani et al Citric acid foliar application improves the total carbohydrate and seed protein content in wheat (Sadak and Orabi, 2015).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…According to Farooq et al (2018), higher concentrations of heavy metals reduce the overall seed protein content in legumes. In addition, albumins and globulins, the seed protein fractions, have been reported to decrease under Cd supply in chickpeas(Ghosh et al, 2022). These findings also validate the conclusions ofChaoui and El Ferjani (2013) and Jaouani et al Citric acid foliar application improves the total carbohydrate and seed protein content in wheat (Sadak and Orabi, 2015).…”
supporting
confidence: 81%
“…Some amino acids, such as proline, accumulate in plants which may help reduce the harmful effects of heavy metal accumulation (Mehta and Gaur, 1999). It has been shown that the levels of the amino acids tryptophan, cysteine, and methionine in protein fractions of chickpea seeds are reduced when exposed to Cd and Pb, as reported by Ghosh et al (2022). Gianazza et al (2007) observed that in Lepidium sativum, Cd was more damaging than Pb in terms of its effect on amino acid content in the seedling.…”
Section: Free Amino Acidsmentioning
confidence: 90%